THE IMPACT OF THE FIFA 11+ ON THE STRUCTURE OF SELECT TRUNK AND LOWER EXTREMITY MUSCLES IN ADOLESCENT FEMALE FOOTBALLERS. Issue 7 (11th March 2014) - Whittaker, J; Emery, CA
Abstract : Background: The FIFA 11+ is an injury prevention program found to reduce lower-extremity injury risk; however, the mechanisms behind this protective effect are not well understood. One possible explanation is the program addresses trunk and lower-extremity muscle deficits. Objective: To determine the impact of FIFA 11+ exposure on the structure of select muscles in adolescent female footballers. Setting: Sport Medicine Clinic. Design: Sub-study embedded within a cluster-randomized controlled trail (RCT). Participants: 23 female footballers (14–16 years) recruited from three teams that participated in a FIFA11+ implementation strategies RCT. Intervention: Participants were recruited from teams randomly assigned to one of two FIFA 11+ delivery groups; coach with unsupervised website access (control; n=11) or, coach with pre-season FIFA 11+ workshop and on-field physiotherapist supervision (comprehensive; n=12). Main outcome measurements: Pre-post season bilateral sonographic measures of: resting Rectus Abdominis (RA), External/Internal Oblique, Transversus Abdominis, Lumbar Multifidus (MF), Gluteus Medius/Minimus (GMd/GMn), and Vastus Mediallis (VM) thickness; VM width and inter-recti distance (IRD); change in abdominal parameters during an Active Straight Leg Raise (ASLR) and gluteals during hip abduction. Mean (95% CI) pre-post season changes in sonographic parameters were calculated and group means compared with paired t-tests (=0.05). Results: No differences in 95% CIs existed for pre-post season change in sonographic parameters between participants with low (mean=149±9 exercises/year) and high (mean=314±15 exercises/year) FIFA 11+ exposure. Both groups exhibited significant within-group IRD decreases at rest (low t=8.20, P<.001; high t=5.90, P<.001) and with the ASLR (low t=5.66, P<.001; high t=5.04, P<.001). Further, the lower exposure group demonstrated decreased ASLR percent RA thickness change (t=3.19, P=.01) while the high exposure group exhibited increased resting MF thickness (t=2.26, P=.04). Conclusions: Different levels of FIFA 11+ exposure in this investigation were not associated with differential changes in the structure of the muscles investigated. Protective mechanisms underlying the FIFA11+ may be associated with alterations in neuromuscular control resulting in IRD and MF adaptations.